2003
DOI: 10.1111/j.1572-0241.2003.07605.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-administered propofol sedation without anesthesia specialists in 9152 endoscopic cases in an ambulatory surgery center

Abstract: Narcotics and benzodiazepines are commonly used for sedation for endoscopy in the United States. Propofol has certain advantages over narcotics and benzodiazepines, but its use is often controlled by anesthesia specialists. This report describes our experience with dosage, safety, patient satisfaction, and discharge time with nurse-administered propofol sedation in 9152 endoscopic cases. The study was performed in a private practice ambulatory surgery center in Medford, Oregon. With the assistance of an anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(52 citation statements)
references
References 21 publications
0
47
0
5
Order By: Relevance
“…In addition, undesirable cardiovascular or respiratory side effects may occur when propofol is used with opioids. Although previous studies have revealed that propofol is safe when given by registered nurses without any involvement by anesthesia specialists, several patients may require a brief period of mask ventilation for the management of prolonged apnea (10,(18)(19)(20). This side effect occurs because of the narrow therapeutic range and the lack of an antidote in cases of over-sedation and subsequent apnea.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, undesirable cardiovascular or respiratory side effects may occur when propofol is used with opioids. Although previous studies have revealed that propofol is safe when given by registered nurses without any involvement by anesthesia specialists, several patients may require a brief period of mask ventilation for the management of prolonged apnea (10,(18)(19)(20). This side effect occurs because of the narrow therapeutic range and the lack of an antidote in cases of over-sedation and subsequent apnea.…”
Section: Discussionmentioning
confidence: 93%
“…A few studies have assessed the safety of physician-and nurse-administered propofol sedation (9,10). However, many practitioners never receive formal instruction in sedation methods.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports of the safe administration of these sedations, even with drugs not specifically approved for this indication, such as propofol [40,41]. However, the majority of the morbidity and mortality related to sedation practice is the result of respiratory compromise.…”
Section: The Role For Cpap During Sedation Remains Poorly Definedmentioning
confidence: 99%
“…A droga ideal para sedação durante os procedimentos endoscópicos deve possuir as seguintes caracterís-ticas: efeito imediato, sedação somente enquanto durar o procedimento, recuperação da consciência rapidamente, sem período residual de desordens mentais ou psicomotoras, e baixa incidência de efeitos colaterais. O uso rotineiro de uma droga de ação curta tem sido recomendado por muitos autores, sendo um meio para aumentar o conforto durante os procedimentos endoscópicos, resultando em procedimento de menor duração com um tempo de recuperação da consciência mais rápido 2,[4][5][6][7][8][9][10] . O propofol (2,6-diisopropylphenol) é agente aprovado pelo Food and Drug Administration (FDA) dos USA, de ação extremamente curta no sistema nervoso central, classificado como droga que promove atividade do ácido gama aminobutírico (GABA) no cérebro, com propriedades sedativas e hipnóticas.…”
unclassified